Optimal exercise modalities and dose for enhancing intelligence in children and adolescents: a Bayesian network meta-analysis - Wang, Yan; Wang, Junyu; Zhang, Lin; Wang, Chengji; Wang, Guotuan; Li, Changdong; Yuan, Yuan; Qiu, Bopeng; Yang, Yong (Frontiers in Physiology, 2026)
BackgroundTo compare the effects of various exercise modalities on intelligence and determine the optimal exercise dose for children and adolescents.MethodsA systematic review and Bayesian network meta-analysis following PRISMA guidelines was conducted. Four databases were searched up to 1 April 2025. Eligible RCTs involved participants aged 5–18 years and assessed exercise interventions with intelligence outcomes (general, fluid, or crystallized). Standardized mean differences (SMDs) with corresponding 95% confidence interval or credible intervals were calculated. Dose-response relationships were analyzed using model-based network meta-analysis.ResultsFifteen RCTs with 3,400 participants were included. Exercise was linked to small-to-moderate improvements in general (SMD = 0.59), fluid (SMD = 0.43), and crystallized intelligence (SMD = 0.64). Dual-task balance training (DTBT) produced the most consistent and significant benefits across all domains. Yoga and multi-component exercise also showed positive effects. Optimal outcomes were achieved with sessions lasting ≥117.7 min, three times weekly, totaling 220 min per week for at least 11.12 weeks. An inverted U-shaped dose-response curve indicated diminishing returns beyond the optimal frequency and duration.ConclusionDTBT is the most effective exercise modality for improving intelligence in children and adolescents. The findings provide evidence-based guidance for designing school and clinical exercise programs to support cognitive development during growth.